A 0.8‐V supply bulk‐driven operational transconductance amplifier and Gm‐C filter in 0.18 µm CMOS process. (6th March 2014) - Abbasalizadeh, Soolmaz; Sheikhaei, Samad; Forouzandeh, Behjat
Summary A low voltage bulk‐driven operational transconductance amplifier (OTA) and its application to implement a tunable Gm‐C filter are presented. The linearity of the proposed OTA is achieved by nonlinear terms cancelation technique, using two paralleled differential topologies with opposite signs in the third‐order harmonic distortion term of the differential output current. The proposed OTA uses 0.8 V supply voltage and consumes 31.2 μW. The proposed OTA shows a total harmonic distortion of better than −40 dB over the tuning range of the transconductance, by applying 800 mVppd sine wave input signal with 1 MHz frequency. The OTA has been used to implement a third‐order low‐pass Gm‐C filter, which can be used for wireless sensor network applications. The filter can operate as the channel select filter and variable gain amplifier, simultaneously. The gain of the filter can be tuned from −1 to 23 dB, which results in power consumptions of 187.2 to 450.6 μW, respectively. The proposed OTA and filter have been simulated in a 0.18 µm CMOS technology. Simulations of process corners and temperature variations are also included in the paper. Copyright © 2014 John Wiley & Sons, Ltd.